A framework of social determinants of health for delirium tailored to older adults. Issue 1 (25th October 2021) - Arias, Franchesca; Alegria, Margarita; Kind, Amy J.; Jones, Richard N.; Travison, Thomas G.; Marcantonio, Edward R.; Schmitt, Eva M.; Fong, Tamara G.; Inouye, Sharon K.
Abstract: Delirium is a debilitating medical condition that disproportionately affects hospitalized older adults and is associated with adverse health outcomes, increased mortality, and high medical costs. Efforts to understand delirium risk in hospitalized older adults have focused on examining medical comorbidities, pre‐existing cognitive deficits, and other clinical and demographic factors present in the period proximate to the hospitalization. The contribution of social determinants of health (SDOH), including social circumstances, environmental characteristics, and early‐life exposures, referred as the social exposome, to delirium risk is poorly understood. Increased knowledge about the influence of SDOH will offer a more comprehensive understanding of factors that may increase vulnerability to delirium and poor outcomes. Clinically, these efforts can guide the development and implementation of holistic preventive strategies to improve clinical outcomes. We propose a SDOH framework for delirium adapted for older adults. We provide the definition, description, and rationale for the domains and variables in our proposed model.